Faktor Determinan Rutur Perineum Derajat I dan III - Erni Dwi Widyana; Afnani Toyibah; Siti Martina (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2019)
Postpartum hemorrhage reaches 50% in Indonesia in 2010. postpartum hemorrhage is an important cause of maternal mortality, especially in developing countries. The things that cause postpartum hemorrhage was atonic uterus, birth canal injury, the release of part of the placenta from the uterus, such as the lagging portion of the placenta or placenta suksenturiata cotyledons. Injury in the birth canal that cause a lot of bleeding is the rupture of the perineum. The research objective was to determine the determinant factors which affect the rupture of the perineum in BPM